2006
DOI: 10.1051/0004-6361:20053853
|View full text |Cite
|
Sign up to set email alerts
|

The supermassive black hole in Centaurus A: a benchmark for gas kinematical measurements

Abstract: We present new HST Space Telescope Imaging Spectrograph observations of the nearby radio galaxy NGC 5128 (Centaurus A). The bright emission line with longest wavelength accessible from HST, [S III]λ9533 Å, was used to study the kinematics of the ionized gas in the nuclear region with a 0. 1 spatial resolution. The STIS data were analized in conjunction with the ground-based near-infrared Very Large Telescope ISAAC spectra used by Marconi et al. (2001, ApJ, 549, 915) to infer the presence of a supermassive bla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
123
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(139 citation statements)
references
References 57 publications
16
123
0
Order By: Relevance
“…The modeling assumes that the gas is rotating in a thin disc configuration (neglecting hydrodynamical effects) under the effect of the gravitational potential of the stellar mass and of a pointlike dark mass M BH that is the BH. The value of M BH and other unknown parameters of the model are obtained by fitting the rotation curves (see Marconi et al (2006) and references therein for details). Because of the many unknown parameters of the model, to better constrain the fit, usually many spectra of the galactic nucleus are obtained each with a different orientation of the spectroscopic slit and a simultaneous fit of all of them is performed.…”
Section: The Standard Gas Kinematical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeling assumes that the gas is rotating in a thin disc configuration (neglecting hydrodynamical effects) under the effect of the gravitational potential of the stellar mass and of a pointlike dark mass M BH that is the BH. The value of M BH and other unknown parameters of the model are obtained by fitting the rotation curves (see Marconi et al (2006) and references therein for details). Because of the many unknown parameters of the model, to better constrain the fit, usually many spectra of the galactic nucleus are obtained each with a different orientation of the spectroscopic slit and a simultaneous fit of all of them is performed.…”
Section: The Standard Gas Kinematical Methodsmentioning
confidence: 99%
“…The reason is very simple and is related to the fact that the full PVD depends on the unknown intrinsic flux distribution of the emission line. Marconi et al (2006) showed that line profiles do depend on the assumed flux distribution while, on the contrary, such dependence is much weaker on the first moment of the line profile (i.e. the mean velocity).…”
Section: Combining Spectroastrometric and Rotation Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the fraction, a radial model for the stellar emission is needed. We adopted the radial luminosity profile given by Marconi et al (2006) who fitted the intensity profile using an oblate spheroidal function. Using this model, we integrated the emission of the radial emission model along each line-of-sight towards the dust features to the point closest to the observer where that line-of-sight connects with the warped disk structure.…”
Section: Dust Geometrymentioning
confidence: 99%
“…• (ground-and spacebased observations of gas kinematics, Marconi et al 2006). The last study also constrained the size of the central massive object c 2006 RAS to r ∼ 0.6 pc suggesting that it is indeed a black hole.…”
Section: Introductionmentioning
confidence: 89%